Group Theater Experiences in the Occupation of the Urban Space in Porto Alegre - Cecilia Lauritzen Jácome Campos (Universidade do Estado de Santa Catarina – UDESC, Florianópolis/SC, Brazil); Vera Lúcia Bertoni dos Santos (Universidade Federal do Rio Grande do Sul – UFRGS, Porto Alegre/RS, Brazil) (Revista Brasileira de Estudos da Presença, 2016)
This article focuses on group theater aspects that take place in the streets, in the city of Porto Alegre, Brazil: its motivations, conditions, and relationships established as a consequence of an urban space occupation through theatrical performances. Through the analysis of discourses from representatives of five theater groups from Porto Alegre (which were collected through a seminar and interviews), in a dialogue with performing arts, history, and anthropology scholars, we reflect on the attempt to occupy the city as an aesthetic choice and on the type of relationship established between theater performances and street audiences, aiming to broaden the understanding of the relationships between the theater and the street in the present times.